Effects of decoupling on land use: an EU wide, regionally differentiated analysis - Wolfgang Britz; Thomas Heckelei; Ignacio Peŕez (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2006)
This paper presents a quantitative analysis of the impacts of the "Luxembourg Compromise" as compared to a continuation of Agenda 2000 to the year 2010. The employed new version of the CAPRI model allows us to represent the different member states' implementations of the CAP reform and to reflect endogenous world market prices based upon a spatial global trade model. The specific contribution of the analysis is a detailed look at the impacts of national differences in the CAP implementation and regional production structures with respect to changes in land allocation. At EU level, cereal areas decrease by about 5% and oilseeds by about 3%. This is paralleled by increases in the set-aside acreage and extensive fodder production. However, significant differences at the regional level can be observed. They are caused mainly by differences in the shares of durum wheat and fodder maize. – – Der vorliegende Beitrag diskutiert EU-weite Auswirkungen der so genannten Luxemburger Beschlüsse im Jahr 2010 im Vergleich zur Agenda 2000. Die der Analyse zugrunde liegenden Simulationsergebnisse basieren auf einer überarbeiteten Version des CAPRI-Modellsystems, das die national unterschiedliche Implementierung des Reformpaketes abbildet und gleichzeitig endogene Preise mittels eines globalen räumlichen Handelsmodells erfasst. Der Schwerpunkt bei der Ergebnisdarstellung bildet die Analyse von Landnutzungsänderungen vor dem Hintergrund regionaler Produktionsstrukturen und der spezifischen nationalen Ausgestaltung der Reform. Während EU-weit die Getreideflächen um ca. 5% sinken und der Ölsaatenanbau um ca. 3% zurückgeht bei gleichzeitiger Ausdehnung von Flächenstilllegung und extensivem Futterbau, zeigen sich deutliche regionale Unterschiede, insbesondere in Abhängigkeit von Flächenanteilen des Hartweizens und des Futtermais (Quelle: verlag).
Keywords: 330; Agrarsubvention; EU-Agrarpolitik; Agrarreform; Wirkungsanalyse; Agrarboden; Räumliche Verteilung; EU-Staaten